Pedagogy, Protests, and Moving Toward Progress - Nannetta Durnell-Uwechue (Central States Communication Association, 2021)
Our world is in constant flux and educators are at the ship’s helm steering toward what former U.S. Representative John Lewis called “good trouble.” However, in many cases, educators lack the training required to be most effective in doing so. As instructors face student demands to address topics on race and social justice, many educators are unsure about how to respond appropriately to the chants of “No Justice, No Peace!” Thus, this essay explores humanistic and pragmatic approaches for doing so in terms of fostering cultural communication competence when incorporating topics on race and social justice issues in the classroom.